Incarceration and Labor Market Conditions of the Underclass in the United States: an Empirical Investigation - Cantekin, Kerem (European journal on criminal policy and research, 2020)
In this paper using both annual time-series data at the federal level as well as annual state-level (balanced) panel data from 1980 to 2017 we investigate the relationship between several labor market variables and the federal and state level incarceration rates in the United States. We find a significant empirical association between the incarceration rate, 10th-percentile real-wage rate, and the unemployment rate, as well as the level of inequality. Specifically, the time-series analysis reveals a significant negative correlation between the incarceration rate and the 10th-percentile wage rate. Moreover, in all time-series regressions, the unemployment rate and the 40%-to-10% wage ratios are both positively correlated with the incarceration rate. In the state-level analysis, panel data regressions indicate that the unemployment rate, income inequality, and unemployment duration are positively associated with incarceration whereas the 10th-percentile wage is negatively correlated with the latter.